Intra and Interobserver Reliability of the New Classification System of Progressive Collapsing Foot Deformity. Issue 2 (April 2022) - Young Lee, Hee; Mansur, Nacime S.; Lalevée, Matthieu; Dibbern, Kevin N.; Myerson, Mark S.; Ellis, Scott J.; Femino, John E.; de Cesar Netto, Cesar
Category: Other Introduction/Purpose: Historical concept of flatfoot as posterior tibial tendon dysfunction (PTTD) has been questioned. Recently, the consensus group published a new classification system and recommended renaming PTTD to Progressive Collapsing Foot Deformity (PCFD). The new PCFD classification could be effective in providing comprehensive information on the deformity. To date, there has been no study reporting intra- and interobserver reliability and the frequency of each class in PCFD classification. Methods: This was a single-center, retrospective study conducted from prospectively collected registry data. A consecutive cohort of PCFD patients evaluated from February 2015 to October 2020 was included, consisting of 92 feet in 84 patients. Classification of each patient was made utilizing characteristic clinical and radiographic findings by three independent observers. Frequencies of each class and subclass were assessed. Intraobserver and interobserver reliabilities were analyzed with Cohen's Kappa and Fleiss' kappa, respectively. Results: Mean sample age was 54.4, 38% was male and 62% were female. 1ABC (25.4%) was most common subclass followed by 1AC (8.7%) and 1ABCD (6.9%). Only small percentage of patients had isolated deformity. Class A was the most frequent component (89.5%), followed by C in 86.2% of the cases. Moderate interobserver reliability (Fleiss` Kappa=0.561, p<0.001, 95% CI 0.528-0.594) was found for overall classification. Very good intraobserver reliability was found (Cohen`s Kappa=0.851, P<0.001, 95% CI 0.777-0.926). Conclusion: Predominantly, 49.3% of patients had a presentation dominantly involving the hindfoot (A) with various combinations of midfoot and/or forefoot deformity (B), (C) with or without subtalar joint involvement (D). Despite limitations due to inherent subjectivity which may account for moderate interobserver agreement, the new system may potentially cover all possible combinations of the PCFD, providing a comprehensive description and guiding treatment in a systematic and individualized manner.